El comic como recurso didáctico para apoyar el proceso de aprendizaje del idioma inglés básico en los estudiantes de tercer grado en la escuela Miguel Riofrío en el periodo septiembre 2017 – junio 2018 - Ulloa Tinoco, Felipe David (2018)
This research work entitled: The comic as a teaching resource to support the process of learning basic English in third grade students at the Miguel Riofrío school in the period September 2017 - June 2018; The general objective is to implement the comic as a didactic resource to improve the learning of the English language in the third year students at the Miguel Riofrío school in the period September 2017 - June 2018; In his Methodology a type of descriptive, correlational and explanatory study is presented; a quantitativequalitative approach; and, a type of quasi-experimental design; the population with which it was made was 25 students and a teacher; the methods used were: descriptive, observational, analytical, synthetic, inductive and deductive; techniques such as the survey, the interview and the test of knowledge; and, instruments such as the questionnaire, guide of questions, and written test; As a result, it was verified that the students did not master the English language and the application of the workshops gave positive results, evidencing an increase in the proficiency of the English language; so we conclude that comics are powerful and motivating didactic resources